Security and tourism development at nature conservation centre Lagos, Nigeria (2017)
Insecurity constitutes a challenge to tourism development globally. Yet, tourism industry is a major contributing factor to the economic development of many nations, with multiplier effects such as the creation of direct and indirect jobs and the enhancement of world’s peace. This study focuses on security and tourism development in Nigeria, using Nature Conservation Centre, Lagos as a case, paying attention to the extent to which the security measures at the Centre contribute to tourists’ security at the Centre, and the promotion of tourism. Quantitative and qualitative approaches were employed in data collection, using such methods as key informant interviews, in-depth interviews, participant observation and questionnaires. A sample size of 146 research participants participated in the study. Analysed data were presented using descriptive statistical tools of frequency counts, percentages and tables, while qualitative data were presented qualitatively. The study established that the management of Nature Conservative Centre is safety conscious, and has put in place safety measures to make tourists feel safe at the Centre. Security personnel are employed, and Complaints Register and other intelligence that are not made known to outsiders are available. The Centre also builds relationship with Lagos State Security Watch, the Nigeria Police via Police Community Relations Committee and community policing. The management is working towards introducing technologically innovative security measures such as E-gate, which will help to synchronise all the security system at the site. Tourists at Nature Conservative Centre feel safe, leading to an improvement in patronage. Improving on security at the Centre requires more training for security personnel, improvement on security information at strategic places, and provision of feedback on security measures. Tourists are likely to visit destinations where their lives and property are safe, while providing them with relaxation, recreation and memorable experience.